Synthesis, characterization and biological activity of a Schiff base derived from o-amino benzoic acid and its Co(II), Cd(II) and Ni(II) complexes - Hussein, Tasneem Ibrahim; Ahmed, Musa Abduelrahman; Arbab, Ismail Adam; Ibrahim, Awad Salim; Al-Bratty, Mohamed; Alhazmi, Hassan Ahmed; Najmi, Asim (European Journal of Chemistry, 2020)
Equimolar amounts of imidazoleacetophenone and 2-aminobenzoic acid were combined together and the Schiff base 4(1H-imidazole-yl)acetophenoneanthranilic acid was prepared as a new bidentate complexing agent. The synthesized ligand was reacted with cobalt(II), cadmium(II), and nickel(II) ions yielding air stable complexes. For quantification and characterization purposes, elemental analysis, infrared spectra, electronic spectra, proton nuclear magnetic resonance spectra and mass spectra studies were carried out on the obtained complexes and ligand. Thermogravimetric analysis and magnetic susceptibility measurements were also used for characterization. The ligand IR spectrum showed that the ligand acts as a bidentate coordinates to the metal ions through the nitrogen and oxygen atoms.Measurements of magnetic susceptibility for Ni(II) and Co(II) complexes were found to be 3.4 and 3.8 B.M., respectively, in the range normal for the octahedral geometry. The conductivity measurements revealed that the chelates are non-electrolytes. An in vitro antimicrobial investigation was also carried out for the free ligand and its metal complexes against a number of bacterial and fungal strains, to assess their antimicrobial properties by diffusion technique. Antimicrobial activity of the prepared complexes showed higher activity than the free ligand.